Merger activities in the Farm Credit System: 2002-2020 - Hunt, Haley (Kansas State University, 2022)
The Farm Credit System (FCS or ‘The System’) has been in existence for over a century, fulfilling its mission to serve rural America through consistent stable access to credit and financial products for eligible and creditworthy borrowers. However, the Farm Credit System that existed in 1916 is not the same System that exists today, due to major legislative actions prompted by the agriculture credit crisis of the mid-late 1980s; this resulted in significant merger activity that has continued in the years since. The purpose of the research aims to analyze mergers that have occurred in the Farm Credit System over the past 25 years based on four key indicators following the last material structural and legislative changes to the Farm Credit Act that occurred in 1987 in the wake of significant disruption in agriculture and its primary financial support systems, the FCS notwithstanding. Asset size, operating expense ratio, return on equity and average spread are evaluated for statistical significance using a regression model and economic theory. This research is based on time series data from 2002 to 2020 procured from Farm Credit Administration (FCA) call reports comprised of consistently reported financial data by all System institutions on a routine basis to FCA, the regulatory authority for the Farm Credit System. A total of two models with two permutations were estimated as part of this study, that yielded significant findings related to some, but not all of the key indicators. The first model is an individual analysis of each of the four key indicatorss characterized as strong or weak, a total of eight independent variables.. For the second model, the same 4 key indicators were analyzed on a differential basis within each ‘dyad’ (i.e. a pairing of two unique associaions), with a total of four independent variables. A numeric and percentage interpretation was estimated for each model. Statistically significant findings were identified for two of the four key indicators, and the concluding analysis will comprehensively explore each significant finding at length.
Keywords: Agribusiness; Merger; Farm Credit Act; Return on equity; Strategy